PERAN PEMBELAJARAN IPS DALAM MENINGKATKAN KEPEDULIAN SOSIAL SISWA KELAS V SD - Lailatul Khomariyah; Lailiatur Riefa'ah; Sailir Rohmah; Sri Rahmawati; Priyono Tri Febrianto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to explain how Social Studies (IPS) instruction enhances the social awareness of fifth-grade elementary school students. Through a literature review based on various relevant scientific articles, this study employs a qualitative methodology with a descriptive research design. Documentation was used to collect data, and qualitative descriptive analysis was employed to identify, categorize, compare, and draw conclusions from the various research findings. The findings indicate that Social Studies (IPS) instruction is crucial for fostering social values, including empathy, responsibility, cooperation, and environmental awareness. Students’ social awareness has increased through the use of creative teaching techniques, the integration of character values, and the development of these values in the classroom. Nevertheless, there are still several obstacles to its implementation, such as a lack of diversity in learning strategies and a lack of utilization of the teacher’s role in linking lesson material to students’ real-life experiences. Therefore, to maximize the development of students’ social character, more contextual and participatory innovations are needed in social studies education.